Avaliação da MIC-DV para a decomposição de tecido de peixe e desenvolvimento de sistema para geração de vapor frio em frasco único - Pardinho, Renan Buque (2021)
In this work, microwave-induced combustion in disposable vessel (MIC-DV) was evaluated for the decomposition of fish tissue for the subsequent determination of As, Cd, Cr, Cu, Mn, Pb, Se and V by inductively coupled plasma mass spectrometry (ICP-MS) and Hg in a flow injection system with cold vapor generation coupled with inductively coupled plasma mass spectrometry (FI-CVG-ICP-MS). In addition, a chemical vapor generation system in a disposable vessel (DV-CVG) was proposed, coupled with ICP-MS and atomic absorption spectrometry (AAS) techniques for the determination of Hg. For the development of the method using MIC-DV, the following parameters were evaluated: composition of the absorbing solution (HNO3 and HCl), concentration of HNO3 as an absorbing solution (0.25, 0.5, 1, 3, 5, 7 and 14.4 mol L-¹), sample mass (10, 15, 20, 25 and 30 mg), absorbing solution volume (1, 3, 5 and 7 mL) and successive digestion cycles (2 and 3 times). For the ignition of the sample in the MIC-DV, 40 μL of NH4NO3 10 mol L-¹ were pipetted into a filter paper disc, which was positioned in the quartz holder and the set was inserted in disposable vessel. Before closing, the vessel were purged with O2 for 60 s at a flow rate of 4 L min-¹ and inserted into the microwave oven for irradiation for 30 s. After decomposition by MIC-DV, the digested were stored in a refrigerator until quantification. The results obtained by MIC-DV were compared with those obtained by the methods of microwave-induced combustion (MIC) and microwave assisted wet decomposition (MAWD). The proposed method was applied to 5 samples of fish tissue and to the certified reference material (CRM) of fish liver (DOLT 4) under the following optimized conditions: 5 mL of 0.5 mol L-¹ of HNO3 as an absorbing solution using 10 mg of sample mass with one combustion. Considering the system developed for the determination of Hg (DV-CVG), it uses only the lid of the disposable vessel itself with four holes, which were necessary for the introduction of HCl, NaBH4, carrier gas and for carrying the gas phase from inside the vessel to the determination technique. This system was coupled with the ICP-MS and AAS technique, being called DV-CVG-ICP-MS and DV-CVG-AAS. The agreement for the elements As, Cd, Cr, Hg, Mn, Se and V in the 5 samples and CRM evaluated after the decomposition by MIC-DV, did not show significant difference (ANOVA) when compared with the reference methods and certified values. The MIC-DV limits of quantification (LOQs) for As, Cd, Cr, Hg, Mn, Pb, Se and V were 0.02, 0.05, 0.50, 0.10, 0.19, 0, 7, 0.18, 0.02 μg g-¹, respectively. For As, Cd and Hg, the LOQs were below the maximum limit required by MERCOSUL for fish tissue. The DV-CVG-ICP-MS that uses the adapted cover presented a lower LOQ when compared to the FI-CVG-ICP-MS used as a reference. The LOQs of the system with the adapted lid coupled to ICP-MS and AAS were 0.025 and 1.2 μg g-¹ respectively. Both the MIC-DV method and the DV-CVG systems developed in this work, presented low cost (disregarding the technique used), simplicity of operation, safety for the operator, reduced use of reagents and used for the quality control of inorganic contaminants such as As, Cd, Cr, Hg, Mn, Se and V.